Financial Condition Analysis Based on Profitability Ratios at XYZ Rural Bank in 2020-2022 - Suci Damayanti , Endah; N.N. Sawitri; Wastam Hidayat, Wahyu; Suroso, Sugeng (Dinasti International Journal of Management Science, 2024)
Researchers conducted this research, namely in order to find out how the development of financial performance in terms of profitability ratios using return on equity (ROE) analysis in BPR Banks. The subject used is BPR Bank while the object used in this research is an analysis of financial conditions based on profitability ratio analysis. The type of data used is quantitative data. Data collection methods in this research are interviews and documentation. The results of this research illustrate that the financial performance of BPR Banks from 2020 to 2022 can be said to be quite good because according to the results of the calculations the author has made, the results can reach industry standards for profitability ratios that have been set. Therefore, the development and growth of ROE in BPR Banks from 2020 to 2022 has created an average value of 14.90% and has met the industry standard for profitability ratios that have been set, which is 12.50% and can be categorized in a healthy condition. Keyword: Rural Banks, Profitability Ratios, Return on Equity